The effect of tofacitinib on pneumococcal and influenza vaccine responses in rheumatoid arthritis. Issue 4 (20th March 2015) - Winthrop, Kevin L; Silverfield, Joel; Racewicz, Arthur; Neal, Jeffrey; Lee, Eun Bong; Hrycaj, Pawel; Gomez-Reino, Juan; Soma, Koshika; Mebus, Charles; Wilkinson, Bethanie; Hodge, Jennifer; Fan, Haiyun; et al.
Abstract : Objective: To evaluate tofacitinib's effect upon pneumococcal and influenza vaccine immunogenicity. Methods: We conducted two studies in patients with rheumatoid arthritis using the 23-valent pneumococcal polysaccharide vaccine (PPSV-23) and the 2011–2012 trivalent influenza vaccine. In study A, tofacitinib-naive patients were randomised to tofacitinib 10 mg twice daily or placebo, stratified by background methotrexate and vaccinated 4 weeks later. In study B, patients already receiving tofacitinib 10 mg twice daily (with or without methotrexate) were randomised into two groups: those continuing ('continuous') or interrupting ('withdrawn') tofacitinib for 2 weeks, and then vaccinated 1 week after randomisation. In both studies, titres were measured 35 days after vaccination. Primary endpoints were the proportion of patients achieving a satisfactory response to pneumococcus (twofold or more titre increase against six or more of 12 pneumococcal serotypes) and influenza (fourfold or more titre increase against two or more of three influenza antigens). Results: In study A (N=200), fewer tofacitinib patients (45.1%) developed satisfactory pneumococcal responses versus placebo (68.4%), and pneumococcal titres were lower with tofacitinib (particularly with methotrexate). Similar proportions of tofacitinib-treated and placebo-treated patients developed satisfactory influenza responses (56.9% and 62.2%, respectively), although fewer tofacitinib patients (76.5%) developed protective influenza titres (≥1:40 in two or more of three antigens) versus placebo (91.8%). In study B (N=183), similar proportions of continuous and withdrawn patients had satisfactory responses to PPSV-23 (75.0% and 84.6%, respectively) and influenza (66.3% and 63.7%, respectively). Conclusions: Among patients starting tofacitinib, diminished responsiveness to PPSV-23, but not influenza, was observed, particularly in those taking concomitant methotrexate. Among existing tofacitinib users, temporary drug discontinuation had limited effect upon influenza or PPSV-23 vaccine responses. Trial registration numbers: NCT01359150, NCT00413699 .